Social Media and Sustainable Fashion: A Comparative Study of University Students’ Awareness and Attitudes in Finland and Nepal - Pradhan , Seema; Shrestha, Purnima (My University, 2025)
The rapid growth of fashion industry has intensified environmental and social issues globally, making sustainable fashion essentially crucial. Social media has become a powerful tool in shaping consumer awareness and attitudes. Previous studies emphasizes the significant impact of social media usage on users, however, despite engaging and consuming information related to sustainability, it is still not clear whether students who frequently interact with sustainability contents in social media platforms will be more aware and display positive purchasing attitude towards sustainable fashion. Underpinned by social learning theory, this research explores the role of social media usage in shaping university students’ awareness and purchasing attitudes toward sustainable fashion. SLT explains that individuals learn behaviors and attitudes through observing and imitating others. Therefore, social media serves as a digital learning space where observational learning enhances awareness and understanding of sustainable fashion, thus, influencing consumers’ purchasing attitudes. Moreover, this study examines and compares the levels of sustainable fashion awareness and purchasing attitudes between Finnish and Nepalese university students and answer the research question “What is the influence of social media usage on awareness and purchasing attitudes towards sustainable fashion in Finland and Nepal?” Drawing on a sample of 66 university students from Finland and Nepal, a quantitative research methodology was utilized and online survey questionnaire was chosen as the main data collection technique. The collection of data was done through non-probability purposive sampling from students of both countries which allows the researcher to intentionally select the participants based on pre-defined characteristics relevant to the study’s objectives. The survey includes structured questions rated by a five-point Likert scale to measure social media usage, awareness, and purchasing attitudes toward sustainable fashion and distributed via different channels such as WhatsApp, Instagram, emails, etc. For analyzing the data, IBM SPSS Statistics software has been used, where descriptive statistics, reliability tests, and hypothesis testing through both regression and non-parametric analyses are performed to identify the relationships between the variables. The results of this study highlights the positive influence of social media usage in sustainable fashion awareness, however, the impact of social media usage on purchasing attitudes was weaker in comparison to awareness, indicating that awareness is the bridge between digital influence and consumer attitudes. Therefore, this study reveals that awareness is one of the drivers of positive consumer attitude towards sustainable consumption. Furthermore, this study underscores that there is the significant difference in awareness and purchasing attitudes towards sustainable fashion showing that Finnish students’ awareness and purchasing attitudes toward sustainable fashion were more elevated and greater than Nepali students, suggesting that contextual factors such as availability, affordability and cultural environments shape students’ awareness and purchasing attitudes.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business